Diagnosis Gangguan Sendi Temporomandibular pada Kasus Kehilangan Gigi dengan Metode DC/TMD - Amirah Maritsa; Zahrawi Astrie Ahkam; Aisyah AR; Hasrini Hasrini; Zulkarnain Zulkarnain (Jurnal Rumpun Ilmu Kesehatan, 2022)
Background: Temporomandibular joint disorder (TMD) is characterized by craniofacial pain involving the jaw joint, masticatory muscles, or muscles that innervate the head and neck. The causes of TMD are multifactorial, including tooth loss and bad habits. The new DC/TMD protocol is a TMD examination protocol that is highly recommended for use as a clinical and research protocol for dentists. Objective: This study aims to determine the prevalence of TMD diagnosis results using the DC/TMD method, to determine the types of TMD diseases experienced and their relationship to the status of tooth loss in students. Method: The study used a cross-sectional analytical design with samples that met the inclusion criteria of 150 students aged 19-25 years who were taken by total sampling. The research subjects were asked to agree and sign an informed consent in advance by the researcher. Data were obtained from the results of anamnesis and physical examination with a diagnosis of TMD using the DC/TMD protocol based on the International RDC/TMD Consortium Network which has been translated into Indonesian. The examination data were processed using SPSS statistical software with univariate and bivariate tests. Results: 48% of students had tooth loss, 62% of students were diagnosed with TMD, and the results of the relationship analysis using the chi-square test showed that there was a significant relationship between tooth loss and TMD (p-value = 0.024; p